1967
DOI: 10.2466/pms.1967.24.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Visual Discrimination in the Ferret

Abstract: 4 ferrets were trained to discriminate upright and inverted triangles; on transfer tests they generalized to outline figures, small figures, and isosceles triangles. After training to discriminate an upright triangle from a cross, the ferrets generalized to outline figures, rotated figures, and a background of 2-cm. striae. A number of differences in performance between ferrets and hooded rats are noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The current results agree with Slack's (1966) study showing the ability of two North American river otters to discriminate between shapes, including a circle and triangle. In addition, another mustelid species, the ferret (M. putorius), discriminated between shapes that included an inverted triangle versus an upright triangle and an upright triangle versus a cross (Pollard et al, 1967). Neither Slack (1966) nor Pollard et al (1967) reported the surface area of their stimuli, and an examination of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current results agree with Slack's (1966) study showing the ability of two North American river otters to discriminate between shapes, including a circle and triangle. In addition, another mustelid species, the ferret (M. putorius), discriminated between shapes that included an inverted triangle versus an upright triangle and an upright triangle versus a cross (Pollard et al, 1967). Neither Slack (1966) nor Pollard et al (1967) reported the surface area of their stimuli, and an examination of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand ferrets (Mustela putorius) were able to discriminate a solid upright triangle versus an inverted triangle and an upright triangle versus a cross (Pollard, Beale, Lysons, & Preston, 1967). The discriminations were maintained when the stimuli were modified to outlines or rotated (Pollard et al, 1967). Mink (Mustela vision) and ferrets (Mustela furo) achieved performance similar to primates in a learning-set formation task, although the stimuli varied in brightness, surface area, and thickness in addition to shape (Doty, Jones, & Doty, 1967).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many different terrestrial and aquatic animals have demonstrated the ability to discriminate between 2D or 3D stimuli varying in shape. Mammals that have been tested include dolphins (Harley, Roitblat, & Nachtigall, 1996;von Fersen, Schall, & Gunturken, 2000), sea lions (Mauck & Dehnhardt, 1997;Schusterman & Thomas, 1966), ferrets (Pollard, Beale, Lysons, & Preston, 1967), opossum (James & MacFarland, 1966), rats (Minini & Jeffery, 2006;Oldfield-Box, 1969), monkeys (Tanaka, 2000), and white rhinos (Daniel & Mikulka, 1998). Birds that have displayed the ability to discriminate shape include pigeons (Young, Peissig, & Wasserman, 2001), jungle crows (Bogale & Sugita, 2013), parakeets , and chickens (Zolman, 1969).…”
mentioning
confidence: 99%
“…When they were prevented from using luminance cues, rats seemed to prefer using single features like stimulus width, and used aspect ratio only after prolonged training. Animals that generalize a shape discrimination when stimuli are altered in size, rotated, or translated may be using holistic shape processing (Mauck & Dehnhardt, 1997;Pollard et al, 1967).…”
mentioning
confidence: 99%